PENYUSUNAN INSTRUMEN PENGUKURAN KOMPETENSI NON-TEKNIS BERBASIS WAWANCARA BBI Making of Instrument Non-Technical Competency Assesment Based on Behavior Interview (Behavior Based Interview) in PT. “X” - Yudhi Prasetya; Nurlaila Effendy; L. Verina Halim (CALYPTRA, 2014)
The phenomenon of competition among industry companies is not something new. PT. “X” is one of the food industry are trying to apply human resource management for the company to remain competitive with other similar industries. PT. “X” hope to have competent workers in the field that the worker will be able to contribute in improving operational performance of the company's. In creating a competent worker takes the right steps to develop existing their competencies. Measurement with behavior-based interview (BBI) is one way that can be recommended to the company in order to identify the competencies of workers. Method of data collection in this research using interviews, observations, and discussions with management. The results is an overview of the process to making of guidelines for interview BBI especially non-technical competencies. In general, the things that need to be prepared is to understand the competency dictionary, how to reduce the question of the competence of the company's competency dictionary, and the need for skills such as probing interviews, parafrashing, and others.